Health Care Professionals Happiness and Patient Satisfaction. The case of Physiotherapists - Jacobshon, Lia (2019)
In recent years research on organizational happiness has been increasing but instruments to measure happiness at work, considering organizational factors, are scarce. Previous research demonstrates the positive impact of satisfaction on patient rehabilitation.